Physical activity and all-cause mortality in Korean older adults. (19th May 2018) - Cho, Jinkyung; Lee, Inhwan; Park, Soohyun; Jin, Youngyun; Kim, Donghyun; Kim, Shinuk; Kang, Hyunsik
Abstract: Background: The association between physical activity (PA) and all-cause mortality may be modulated by potential confounders. Aim: To investigate the association between weekly PA and all-cause mortality in a population-based prospective study. Subjects and methods: The study sample included Korean older adults aged 60 years and older who participated in baseline assessments ( n = 15 416) in 2008 and completed follow-up visits in 2011 ( n = 14, 976). Primary outcome was 3-year all-cause mortality. Results: Compared with sufficiently active individuals (with Hazard Ratio (HR) = 1), completely inactive and insufficiently active individuals had a significantly higher risk of all-cause mortality (HR = 2.086, 95% CI = 1.639–2.655, p < 0.00 and HR = 1.644, 95% CI = 1.013–2.668, p = 0.044, respectively), even after adjustments for age and sex, health-related behaviour factors (i.e. smoking, alcohol intake and nutritional risk), cognitive impairment and components of frailty phenotype (i.e. involuntary weight loss, exhaustion and slowness). In addition, the inverse association between PA and all-cause mortality is differently modulated by potential confounders, including age, sex, smoking, depressive symptoms, cognitive impairment and involuntary weight loss. Conclusion: PA was inversely and independently associated with all-cause mortality in Korean older adults.